1990
DOI: 10.1109/23.106689
|View full text |Cite
|
Sign up to set email alerts
|

Iterative image reconstruction for positron emission tomography: a study of convergence and quantitation problems

Abstract: Iterative reconstruction techniques have been shown to have superior noise characteristics compared to conventional filtered backprojection (FB). The main drawbacks of the iterative methods are the increased computational burden and the difficulty in establishing a stopping criterion and ensuring proper quantitation in different imaging situations. Using a combination of techniques, we have been able to reduce the time required for iterative reconstruction to a few times that of FB. We have also compared the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Our results indicate a possible exception when using an MC matrix well matched to the tomograph. The results of Hoke et al [32], Llacer and Bajamonde [33], Liow and Strother [34], and Herman and Odhner [24] are all verified by our work. We find our results difficult to reconcile with those of Politte and Snyder [9].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our results indicate a possible exception when using an MC matrix well matched to the tomograph. The results of Hoke et al [32], Llacer and Bajamonde [33], Liow and Strother [34], and Herman and Odhner [24] are all verified by our work. We find our results difficult to reconcile with those of Politte and Snyder [9].…”
Section: Discussionsupporting
confidence: 76%
“…For the highly modified MLE algorithm, they decided to stop at a fixed number of iterations. Holte et al [32] investigated the behavior of the MLE algorithm principally in cold spots. They found that noise in regions of low counts was lower than in regions of high counts, and that by iterating to a point where the high-count regions exhibited substantial noise, quantitation of cold spots was excellent.…”
Section: Bias and Variance Analysismentioning
confidence: 99%
“…While both theory and experiment indicate the monotonic increase of the likelihood function in the EM method, it is well-known that stopping at a smaller likelihood value, i.e. not at the maximum for the likelihood, can give a higher quality solution [6][7][8][9]. Stopping the iteration before convergence in this way is necessary but appears to conflict with the appropriate notation for PET imaging is provided.…”
Section: Introductionmentioning
confidence: 97%
“…Iterative approaches include maximum likelihood-expectation maximization (ML-EM) and ordered subsets expectation maximization (OSEM). ML-EM imaging generates higher-quality images than FBP, with less noise (3)(4)(5). However, the disadvantage of ML-EM is that it requires long convergence time.…”
Section: Introductionmentioning
confidence: 99%